Relative Contribution of Insulin and Its Precursors to Fibrinogen and PAI-1 in a Large Population With Different States of Glucose Tolerance: The Insulin Resistance Atherosclerosis Study (IRAS) - Festa, Andreas; D'Agostino, Ralph; Mykkanen, Leena; Tracy, Russell P.; Zaccaro, Daniel J.; Hales, C. Nick; Haffner, Steven M. (Arteriosclerosis, thrombosis, and vascular biology, 1999)
Hyperinsulinemia is associated with the development of coronary heart disease. However, the underlying mechanisms are still poorly understood. Hypercoagulability and impaired fibrinolysis are possible candidates linking hyperinsulinism with atherosclerotic disease, and it has been suggested that proinsulin rather than insulin is the crucial pathophysiological agent. The aim of this study was to investigate the relationship of insulin and its precursors to markers of coagulation and fibrinolysis in a large triethnic population. A strong and independent relationship between plasminogen activator inhibitor-1 (PAI-1) antigen and insulin and its precursors (proinsulin, 32-33 split proinsulin) was found consistently across varying states of glucose tolerance (PAI-1 versus fasting insulin [proinsulin], r=0.38 [r=0.34] in normal glucose tolerance; r=0.42 [r=0.43] in impaired glucose tolerance; and r=0.38 [r=0.26] in type 2 diabetes; all P<0.001). The relationship remained highly significant even after accounting for insulin sensitivity as measured by a frequently sampled intravenous glucose tolerance test. In a stepwise multiple regression model after adjusting for age, sex, ethnicity, and clinic, both insulin and its precursors were significantly associated with PAI-1 levels. The relationship between fibrinogen and insulin and its precursors was significant in the overall population (r=0.20 for insulin and proinsulin; each P<0.001) but showed a more inconsistent pattern in subgroup analysis and after adjustments for demographic and metabolic variables. Stepwise multiple regression analysis showed that proinsulin (split products) but not fasting insulin significantly contributed to fibrinogen levels after adjustment for age, sex, clinic, and ethnicity. Decreased insulin sensitivity was independently associated with higher PAI-1 and fibrinogen levels. In summary, we were able to demonstrate an independent relationship of 2 crucial factors of hemostasis, fibrinogen and PAI-1, to insulin and its precursors. These findings may have important clinical implications in the risk assessment and prevention of macrovascular disease, not only in patients with overt diabetes but also in nondiabetic subjects who are hyperinsulinemic. (Arterioscler Thromb Vasc Biol. 1999;19:562-568.)